2010
DOI: 10.1186/1751-0147-52-64
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal motor activity during anaesthesia in a dog: a case report

Abstract: Seizures or convulsions that occur during anaesthesia in veterinary patients are infrequently reported in the literature. Consequently, the incidence of such events is unknown. Several drugs commonly used in clinical veterinary anaesthesia have been shown to induce epileptiform activity in both human clinical patients and experimental candidates. The present case report describes convulsions in a four-year old male Bernese mountain dog during maintenance of anaesthesia with isoflurane after premedication with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The effect is consistent with the proconvulsant properties reported for ketamine [31,32] during anaesthesia involving both humans [29] and animals (mostly dogs: [31,32]). Ketamine increases the release of endogenous excitatory amino acids such as glutamate and aspartate [36] and is generically contraindicated for animals with pre-existing seizure disorders.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The effect is consistent with the proconvulsant properties reported for ketamine [31,32] during anaesthesia involving both humans [29] and animals (mostly dogs: [31,32]). Ketamine increases the release of endogenous excitatory amino acids such as glutamate and aspartate [36] and is generically contraindicated for animals with pre-existing seizure disorders.…”
Section: Discussionsupporting
confidence: 88%
“…In geriatric badgers > 8 yrs old, ketamine appeared to induce tonic-clonic seizures in some individuals, as noted in susceptible humans [29] and dogs [30,31,32]. Furthermore, all four (repeatedly) affected individuals were females, where Monteiro et al [33] report that female dogs are prone to more frequent cluster seizures than males, possibly due to pro-convulsan effects of oestrogen which enhances neuronal excitability [34].…”
Section: Discussionmentioning
confidence: 94%
“…Subjectively, the authors have not yet observed significant adverse effects associated with KET 5 mg/kg IV bolus when used for prolonged seizure activity. KET has been reported to have potentially a proconvulsant effect in veterinary patients, with up to 20% of cats in one study and reports of dogs developing seizures after induction with KET IV ( 71 – 73 ). The reasons why KET may be proconvulsant for some patients are not completely understood, but a genetic pre-disposition may exist, since a phenotypic pre-disposition was described in the feline cohort with only all of the cats with prominent black or dark brown stripes on their hair coat developing seizures ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ketamine in canine epilepsy has undergone a paradigm shift in recent years. Historically, it has been suggested to avoid ketamine in epileptic humans and dogs due to its proconvulsive properties (1)(2)(3)(4)(5), but in recent years, ketamine has been increasingly promoted as a game changer for status epilepticus in human (6)(7)(8)(9) as well as in veterinary medicine (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This electroconvulsive phenomenon coincided with the peak concentration of ketamine in the arterial blood. This finding, together with case reports of dogs experiencing seizure after ketamine administration, most likely contributed to the fact that people were reluctant to use ketamine in epileptic animals (4,5).…”
Section: Introductionmentioning
confidence: 99%